Penerapan Media Gambar Suku Kata Dalam Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas I - Tinny Mery Jones Walangare (Education Reserach Center, 2025)
This study aims to enhance the initial reading ability of first-grade students at SDN Sawunggaling I/382 Surabaya through the implementation of the syllable approach. The research method used is Classroom Action Research (CAR), conducted over three cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The syllable approach is utilized as a teaching method to help students recognize and read syllables, then combine them into words and sentences. Data were collected through observations, learning outcome tests, and field notes. The results indicate a significant improvement in students' initial reading abilities across all cycles. The average test scores increased from 63.5 in Cycle I to 67.75 in Cycle II, and reached 73.25 in Cycle III. In addition to improved scores, there was also an increase in students' activeness, motivation, and participation in the learning process. The application of the syllable approach proved effective in gradually training students to read and strengthening their understanding of language structure. This study highlights the importance of appropriate teaching strategies in enhancing students' literacy skills from an early age. The syllable approach, supported by diverse media and activities, not only helps students master reading skills but also boosts their confidence and interest in learning. This research is expected to serve as a reference for teachers and education practitioners in developing more innovative and effective reading instruction methods